2014
DOI: 10.1186/s12859-014-0350-x
|View full text |Cite
|
Sign up to set email alerts
|

Using phylogenetically-informed annotation (PIA) to search for light-interacting genes in transcriptomes from non-model organisms

Abstract: BackgroundTools for high throughput sequencing and de novo assembly make the analysis of transcriptomes (i.e. the suite of genes expressed in a tissue) feasible for almost any organism. Yet a challenge for biologists is that it can be difficult to assign identities to gene sequences, especially from non-model organisms. Phylogenetic analyses are one useful method for assigning identities to these sequences, but such methods tend to be time-consuming because of the need to re-calculate trees for every gene of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 93 publications
3
67
0
Order By: Relevance
“…Additionally, opsin expression by itself is weak evidence for the ability of skin to detect light. Other essential r-opsin cascade genes, including G-protein α (q) and phospholipase C, are also expressed in the skin of O. bimaculoides, suggesting that the necessary genes for functional opsin-based phototransduction are expressed in octopus skin (Speiser et al, 2014). Finally, the LACE action spectrum is also consistent with our hypothesis.…”
Section: Discussionsupporting
confidence: 77%
“…Additionally, opsin expression by itself is weak evidence for the ability of skin to detect light. Other essential r-opsin cascade genes, including G-protein α (q) and phospholipase C, are also expressed in the skin of O. bimaculoides, suggesting that the necessary genes for functional opsin-based phototransduction are expressed in octopus skin (Speiser et al, 2014). Finally, the LACE action spectrum is also consistent with our hypothesis.…”
Section: Discussionsupporting
confidence: 77%
“…Additionally, we used PIA (Speiser et al . ) with default parameters to identify opsins that could be missed by the HMMER search using raw Trinity transcriptomes. All redundant (identical) opsin sequences identified by both approaches were removed using CD‐HIT.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study we report that in a transcriptome analysis of ME (Speiser et al, 2014), we detected two rhabdomeric opsins (r-opsins) that had not been identified previously in transcriptomes of VE and LE, and in a BLAST analysis of a recent assembly of the Limulus genome (http://www.ncbi.nlm.nih.gov/bioproject/ PRJNA20489), we detected an additional r-opsin sequence closely related to one found in the ME transcriptome. We call these opsins LpOps6, LpOps7 and LpOps8.…”
Section: Introductionmentioning
confidence: 84%